A fire-safe Li metal battery via smart gas management - Jun-Chen Guo; Cong-Zheng Chai; Ya-Hui Wang; Yao Zhao; Sen Xin; Ying Zhang; Yu-Guo Guo; Chunli Bai (Proceedings of the National Academy of Sciences, 2025)
Lithium (Li) metal batteries offer high energy density but face significant safety challenges due to gas evolution under thermal abuse conditions. At the anode, the reduction of organic carbonate-based electrolytes generates flammable gases (e.g., H 2 , CH 4 ), while the poor thermal stability of the cathode results in the release of O 2 , CO, and CO 2 . The accumulation of these gases contributes to mechanical rupture, and their migration further exacerbates thermal runaway. To address these challenges, we propose a smart gas management strategy that constructs continuous flame-retardant interfaces (FRIs) by incorporating flame-retardant polymers (FRPs) into the cathode. Smart gas management is defined as the ability to suppress gas production, alter gas composition to reduce flammability, and mitigate internal pressure buildup, thereby preventing thermal runaway. The FRIs significantly enhance the thermal stability of the cathode by suppressing oxygen release and minimizing electrolyte oxidation caused by active oxygen species. Additionally, the FRP releases flame-retardant radicals that diffuse into the electrolyte, interrupting reactions that generate flammable gases at the anode. This dual-action mechanism reduces gas production and mitigates the risks associated with thermal runaway, forming the foundation of a smart gas management strategy. With this strategy, we demonstrate zero thermal runaway in a 0.58-Ah Li||NCM811 pouch cell with 100% state of charge under thermal abuse conditions. This approach is highly compatible with current manufacturing processes, offering a scalable solution for improving the safety of high-energy-density Li metal batteries. This work provides a promising pathway toward fire-safe Li metal batteries for electric vehicles and other energy storage applications.